The Influence of Situational Leadership Style and Work Orientations on Employee Performance in Jakarta Islamic Banking Industry - Junaedi, Edy; Ali, Juhary (ITQAN: Journal of Islamic Economics, Management, and Finance, 2025)
Leadership style has a strategic role in increasing employee performance, especially in the Islamic banking sector. This study examines the influence of leadership style and work orientation on employee performance in the Islamic banking industry in Jakarta. This study uses a quantitative method with a descriptive approach with a questionnaire as the main instrument, tested for validity and reliability through a preliminary trial. This research used a purposive sampling technique; data was collected from 364 employees from 12 Islamic commercial banks and Islamic business units. Data were analyzed using the PARTIAL least Square Sequential Equation Model (PLS-SEM) method. The results of the study found that situational leadership style has a significant influence on employee performance. In addition, work orientation also has a significant influence on improving performance. These findings indicate that leaders in Islamic banking need to encourage innovation, listen to employee expectations, and communicate effectively to achieve optimal performance. In this study, adjusting leadership style to the unique context of Islamic banking has been shown to increase employee productivity. Organizations in the Islamic banking sector are advised to adopt an inclusive leadership style and focus on developing a culture of innovation to drive better results.